Galectin-12 enhances inflammation by promoting M1 polarization of macrophages and reduces insulin sensitivity in adipocytes. (3rd August 2016) - Wan, Lei; Lin, Hui-Ju; Huang, Chi-Chun; Chen, Ying-Chi; Hsu, Yu-An; Lin, Chia-Hung; Lin, Hsiu-Chu; Chang, Ching-Yao; Huang, Su-Hua; Lin, Jane-Ming; Liu, Fu-Tong
Abstract: Galectin-12 is a member of an animal lectin family with affinity for β-galactosides and containing consensus amino acid sequences. Here, we found that galectin-12 was expressed in macrophages and thus aimed to determine how galectin-12 affects inflammation and macrophage polarization and activation. The ablation of galectin-12 did not affect bone marrow cells to differentiate into macrophages, but reduced phagocytic activity against Escherichia coli and lowered the secretion of nitric oxide. The ablation of galectin-12 also resulted in the polarization of macrophages into the M2 direction, as indicated by increases in the levels of M2 markers, namely, resistin-like β (FIZZ1) and chitinase 3-like 3 (Ym1), as well as a reduction in the expression levels of a number of M1 pro-inflammatory cytokines. We found that the diminished expression of pro-inflammatory cytokines in macrophages resulting from galectin-12 deletion was due to reduced activation of IKKα/β, Akt and ERK, which in turn caused decreased activation of NF-κB and activator protein 1. The activation of STAT3 was much higher in Gal12 −/− macrophages activated by lipopolysaccharide, which was correlated with higher levels of IL-10. Adipocytes showed higher insulin sensitivity when treated with Gal12 −/− macrophage-conditioned media than those treated with Gal12 +/+ macrophages. We conclude galectin-12 negatively regulates macrophage polarization into the M2 population, resulting in enhanced inflammatory responses and also in turn causing decreased insulin sensitivity in adipocytes. This has implications in the treatment of a wide spectrum of metabolic disorders.